DEVELOPMENT OF MEASURES TO INCREASE THE ECOLOGICAL SAFETY OF DRINKING WATER SUPPLY FOR POPULATION OF EASTERN UKRAINE DUE TO THE USE OF BUCHAK-KANIV AQUIFER GROUNDWATER - Levoniuk, S.; Udalov, І. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
In the article, measures to increase the ecological safety of population drinking water supply due to the use of Buchak-Kaniv aquifer groundwater from urban water intakes in Eastern Ukraine have been developed. The ecological consequences of man-made intervention in Buchak-Kaniv aquifer drinking groundwater at the research territory have been assessed. The main pollutant elements of these groundwater have been traced. Water intakes (Poltava, Karlivka, Krasnograd, Lubny, Khorol, Reshetylivka), where the ecological consequences of technogenic intervention in the underground hydrosphere are the greatest, since here the target groundwater is partially or completely unsuitable for drinking purposes, have been identified. The key role of technogenesis (intensification of groundwater withdrawal and expansion of water intakes network; as a result – changes in the hydrodynamic conditions of operational aquifers and formation of their regional depression funnels) in these processes has been established. It is emphasized that the increased content of investigated pollutant elements in systematically consumed drinking water has a colossal effect on the human body, which can be expressed in a number of serious diseases. In the paper, measures have been developed to minimize the established ecological consequences of technogenesis of Buchak-Kaniv aquifer drinking groundwater to increase the ecological safety of population drinking water supply from the Poltava city agglomeration water intakes, which are strategically important for the studied region. The system of groundwater hydrogeochemical monitoring at the region water intakes has been improved for the conditions of filtration of pollutants from the surface or their migration from below in the zones affected by tectonic faults associated with salt diapirs. This significantly shortens the time and reduces the cost of works in comparison with a full complex of hydrogeochemical studies within the entire territory. The allocation of promising areas for the construction of new water intakes to solve the problem of drinking groundwater lack of acceptable quality within the research territory has been substantiated. Estimated resources of high-quality drinking groundwater in a radius of 40 km around the Poltava city, the involvement of which will allow providing high-quality drinking water to the population of this urban agglomeration. The optimal general water withdrawal at the Poltava water intakes to stabilize the content of polluting elements in the composition of Buchak-Kaniv aquifer groundwater within different parts of the city has been justified.
Keywords: groundwater; pollution; environmental safety; water intakes; measures